Assessing clenbuterol’s modulation of metabolic and inflammatory pathways in Nile tilapia (Oreochromas niloticous) fed high fat diet - Aya G. Rashwan; Doaa H. Assar; Abdallah S. Salah; Muyassar H. Abualreesh; Shimaa M. R. Salem; Norah Althobaiti; Zizy I. Elbialy (Scientific Reports, 2025)
Abstract This study was performed to reveal the metabolic effects and molecular mechanisms that govern the dietary incorporation of clenbuterol on growth performance, haemato-biochemical changes, histological alteration, and gene expression regulating glucose and lipid metabolism in normal and high-fat diets fed in Nile tilapia (Oreochromis niloticus). Six experimental diets were formulated, incorporating different concentrations of clenbuterol. The 1st three groups were supplemented with a diet comprising 6% fat, with clenbuterol of 0, 5, and 10 g/kg diet was designated as F6 clenb0, F6clenb5, and F6clenb10, respectively. The other treatment groups were fed a diet of 12% fat, with clenbuterol 0, 5, and 10 g/kg diet, respectively termed F12 clenb0, F12 clenb5, and F12 clenb10. The results revealed that compared to the control group, HFD exhibited a marked reduction in FBW, BWG, PER, and body protein percent but significantly increased the FCR, IPF, liver fat percent, and body ash percent with altered hematological parameters, raised serum biomarkers of hepatic and renal injury. HFD signally raised mRNA expression of pro-inflammatory cytokines, and declined nrf2 and antioxidative function-related genes. Also increased mRNA expression of lipogenic genes as FAS and SREBP-1c and gluconeogenic genes as pepck and g6pc while downregulated, pparα, cpt1, acox1. Nevertheless, clenbuterol supplementation significantly reversed the aforementioned findings induced by HFD. Clenbuterol inclusion significantly improves growth performance and antioxidant defenses by modulating nrf2 signaling and reducing inflammatory response, reduces fatty acid synthesis, and enhances mitochondrial β-oxidation not only functioning as a lipid regulator and effectively alleviating fat accumulation in the liver but playing an essential role in the control of glucose metabolism by reducing hepatic glucose production in high-fat diet-fed Nile tilapias well.